Synthesis, Crystal Structure and Magnetic Properties of Heteropolynuclear ReIVMII Complexes Based on the Robust [ReCl5(pyzCOO)]2– Unit (pyzCOO = 2‐pyrazinecarboxylate)1. Issue 12 (24th March 2016) - Arizaga, Livia; González, Ricardo; Armentano, Donatella; De Munno, Giovanni; Novak, Miguel A.; Lloret, Francesc; Julve, Miguel; Kremer, Carlos; Chiozzone, Raúl
Abstract: The syntheses, crystal structures and magnetic properties of four rhenium(IV) compounds of formulae NBu4 [ReCl5 (pyzCOOH)]· H2 O (1 ), [ReCl5 (µ‐pyzCOO)M(dmphen)2 ]· 2CH3 CN [M = Ni (2 ) and Co (3 )] and {[ReCl5 (µ3 ‐pyzCOO)]2 Mn2 (dmphen)3 } n (4 ) (NBu4 = tetra‐ n ‐butylammonium cation, pyzCOOH = 2‐pyrazinecarboxylic acid, dmphen = 2, 9‐dimethyl‐1, 10‐phenanthroline) are reported herein. Compound1 was obtained by the reaction of NBu4 [ReCl5 (dmf)] (dmf = dimethylformamide) with pyzCOOH in acetone, whereas the other complexes were obtained by the reaction of1 with M(ClO4 )2 · 6H2 O [M = Ni (2 ), Co (3 ), Mn (4 )] and dmphen in acetonitrile. Complex1 is a mononuclear compound, 2 and3 are neutral heterodinuclear complexes and4 is a neutral chain in which each pyzCOO – bridges one Re IV and two Mn II in a very unusual µ3 ‐binding mode. Compounds2 and3 behave as magnetically isolated species with intramolecular ferromagnetic coupling between Re IV and Ni II or Re IV and Co II ions, respectively. In turn, weak antiferromagnetic coupling between the Mn II ions through anti‐syn ‐carboxylate bridges together with weak ferromagnetism below 3.1 K due to small spin canting is observed in4 . Abstract : Three 2‐pyrazinecarboxylate‐bridged Re IV M II compounds [M = Ni (2 ), Co (3 ), Mn (4 )] have been synthesized from the mononuclear complex NBu4 [Re IV Cl5 (pyzCOOH)]· H2 O (1 ). Ferromagnetic interactions between Re IV and M II occurs in2 and3 whereas spin canting and magnetic ordering is observed for4 below 3.1 K.